Bone grafting in the pre-antiseptic era(historical review):Creation of the first theories related to bone grafting: 1860-1880. - Pankratov, Alexander; Shaikhaliev , Astemir (Medicina Historica, 2023)
This article examines the period of formation of the theoretical foundations of bone plastic surgery, and the ideas about bone regeneration in general, which predetermined the development of this branchsection of medical science in the following decades. The work covers the period from L. Ollier’s experimental work to Operation W. Macewen’s operationMacewen (1881). At thethat time, there was a lively debatediscussion in the scientific literature, both regarding the fate of the transplanted bone fragment and about the sources of bone tissueregenerative regeneration. of bone tissue. Microscopic techniques have beenwere used for the first time to study this process, albeitalthough in a limited number of observations. The article analysesanalyzes the arguments of each of the parties involved in the debatediscussion. Although no general concept was developed at that time, the accumulated facts formed the basis forof subsequent clinical experiments made possible by the introduction of an antiseptic approach toin surgical practice.